(5y-3x)/3=x-y

Simple and best practice solution for (5y-3x)/3=x-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5y-3x)/3=x-y equation:


x in (-oo:+oo)

(5*y-(3*x))/3 = x-y // - x-y

(5*y-(3*x))/3-x+y = 0

(5*y-3*x)/3-x+y = 0

(5*y-3*x)/3+(3*(-x))/3+(3*y)/3 = 0

3*(-x)-3*x+5*y+3*y = 0

5*y-6*x+3*y = 0

8*y-6*x = 0

(8*y-6*x)/3 = 0

(8*y-6*x)/3 = 0 // * 3

8*y-6*x = 0

8*y-6*x = 0 // - 8*y

-6*x = -(8*y) // : -6

x = (-(8*y))/(-6)

x = (4*y)/3

x = (4*y)/3

See similar equations:

| 45=23+x | | 40=9/5c | | Y=7Sin(6x+5)+2Cos(3x-2) | | 5x-(-2x+1)=2 | | 2x+6+x+1=3(x-1)+6 | | 3x^2-8y^2=-5 | | 2/10➗3/100 | | 0=-18v^2+1476v-26600 | | 3(x-3)+4=2[-(x-5)-4(2x+1)] | | 4a^2+4a=-15 | | 4a^2+4=-15 | | 2x^1-1=0 | | 5x+60=5x | | 449/0.42= | | 16/5-20x=8 | | 2500+100x+x^2= | | log(5x+1)=1.2 | | y8/y3 | | 6+k^7=-2 | | 3x^3-5x-1=0 | | (36x^4+9)=0 | | 0.05(0.3x-0.06)= | | logx^729=3 | | 4n+5=2n+8 | | logx^36=2 | | 4y+49=27y+7 | | 4y+36=27y+7 | | 4.8x-4=4(1.2x-1) | | 4y+1636=27y+7 | | 8x-5x=x+8 | | 4y+25=27y+7 | | 4y+16=27y+7 |

Equations solver categories